1976
DOI: 10.1042/bj1530165
|View full text |Cite
|
Sign up to set email alerts
|

Properties of the testicular lactate dehydrogenase isoenzyme

Abstract: 1. Studies were carried out with pure lactate dehydrogenase isoenzymes C4 (LDH isoenzyme X), B4, (LDH isoenzyme 1) and A4 (LDH isoenzyme 5) isolated from mouse testis, heart and muscle tissue respectively; with LDH isoenzyme X purified from pigeon testes and with crude lysates of spermatozoa from man, bull and rabbit. 2. LDH isoenzyme X from all species showed greater ability than the other isoenzymes to catalyse the NAD+-linked interconversions of 2-oxobutanoate into 2-hydroxybutanoate and of 2-oxopentanoate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
57
0

Year Published

1978
1978
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 102 publications
(63 citation statements)
references
References 23 publications
6
57
0
Order By: Relevance
“…5A), showed a major protein species that copurified with the dioxygenase-GST fusion protein bound to glutathioneSepharose. MALDI-MS analysis of the protein excised from the SDS-PAGE gel identified the protein as an atypical testisspecific LDH-C. LDH-C was originally identified in the 1960s and demonstrated to catalyze the reversible oxidation of lactate and other secondary alcohols (45,46). However, the physiologic role of this enzyme has often been questioned because the other widely distributed lactate dehydrogenase species (LDH-A and LDH-B) are both highly expressed in the testis (45,46).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…5A), showed a major protein species that copurified with the dioxygenase-GST fusion protein bound to glutathioneSepharose. MALDI-MS analysis of the protein excised from the SDS-PAGE gel identified the protein as an atypical testisspecific LDH-C. LDH-C was originally identified in the 1960s and demonstrated to catalyze the reversible oxidation of lactate and other secondary alcohols (45,46). However, the physiologic role of this enzyme has often been questioned because the other widely distributed lactate dehydrogenase species (LDH-A and LDH-B) are both highly expressed in the testis (45,46).…”
Section: Discussionmentioning
confidence: 99%
“…MALDI-MS analysis of the protein excised from the SDS-PAGE gel identified the protein as an atypical testisspecific LDH-C. LDH-C was originally identified in the 1960s and demonstrated to catalyze the reversible oxidation of lactate and other secondary alcohols (45,46). However, the physiologic role of this enzyme has often been questioned because the other widely distributed lactate dehydrogenase species (LDH-A and LDH-B) are both highly expressed in the testis (45,46). We are unable to find in the literature any information as to whether LDH-C will catalyze either the oxidation or the reduction of aldehydes like retinal, the product of ␤-carotene cleavage.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that testicular LDH-X catalyses preferentially lactate oxidation and is localized in cytosol and mitochondria (Blanco, Burgos, Gérez de Burgos & Montamat, 1976;. This, as well as the localization of mitochondria in early round spermatids close to the cell surface (Clermont & Rambourg, 1978) (Palombi et al, 1979 (Donahue & Stern, 1968 (Biggers, Whittingham & Donahue, 1967;Zeilmaker & Verhamme, 1974;Hillensjö, Hamberger & Ahrén, 1975;Eppig, 1976), but growing oocytes can survive in the absence of pyruvate when cultured in the presence of follicular granulosa cells (Baran & Bachvarova, 1977;Eppig, 1977;Bachvarova, Baran & Tejblum, 1980 …”
Section: Introductionmentioning
confidence: 99%
“…Any variation in phosphoglycerate kinase activity to the extent shown by lactate dehydrogenase C, with respect to the A, or B4 isoenzymes [I 51 could severely restrict carbohydrate metabolism in the sperm. Because of its substrate variability lactate dehydrogenase may be involved in a reducing equivalents shuttle [37].…”
Section: Discussionmentioning
confidence: 99%